How Product Attributes Affect Consumer Decision To Purchase A Premium Scooter Matic? - Yudi Helfi; Fatihatul Akbar; Dinda Mutiara Pratiwi; Fakhri Mujahid Maolani (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2019)
The automotive industry is one of the industries with the largest growth rate in Indonesia. The motorcycle is chosen as the most favorite means of transportation due to their superiority in affordability, maintenance costs, fuel costs and effectiveness of travel time. Among companies that compete fiercely for this market niche are PT. Astra Honda and PT. Yamaha Indonesia Motor Manufacturing. Both of them recently launched a new variant in the premium automatic scooter segment namely Yamaha NMax 155 cc and Honda PCX 150 cc. Although Honda dominates the scooter market segment in general, the AISI data in the early semester of 2018 shows that the achievement of sales of Honda PCX is far behind their closest competitor, Yamaha NMax in the range of 2:8. So that it becomes interesting for the researchers to know the perceptions of quality, features, style, and design of Honda PCX's attributes on consumer decisions in purchasing related products. Respondents involved in this study were 60 members of the HPCI (KAPURSUCI) community, Purwakarta, Subang and Cikarang using non-probability sampling techniques, which is accidental sampling on filling each questionnaire. The results of this study conclude that there is a positive influence between product attributes possessed by Honda PCX (quality, features, and product design) on the purchasing decisions.